Kebijakan Pemerintah Dalam Mengatasi Kelangkaan Gas LPG Subsidi di Indonesia - Lestari, Lutfiani Dwi; Rahmawati, Meita Dwi; Hasna, Minhatul (Journal of Economics and Social Sciences (JESS), 2023)
Introduction: Recently, there has been a shortage of 3 kg subsidized LGP gas which has impacted lower middle class people who have difficulty getting 3 kg subsidized LPG gas from the government. This research aims to analyze how government policies address the problem of subsidized LPG gas scarcity in Indonesia. Research Methods: This method uses a qualitative descriptive analysis approach from books, journal articles and previous research. Results: The research results show that to overcome this scarcity problem, the government issued several policies to overcome the scarcity of subsidized gas, including increasing subsidized gas supplies in several areas, revoking fraudulent agents' permits, market operations in several areas, purchasing subsidized gas by bringing an ID card, strengthening distribution control, limiting purchases of subsidized gas, managing stock well, determining the right price according to market prices, and reviewing revise subsidy policies so that they remain sustainable and efficient. Conclusion: The government must consistently monitor the market, and the public must use subsidized 3 kg LPG gas wisely and not hoard it.